Activation and deformation of immobilized lipase on self-assembled monolayers with tailored wettability1. Issue 20 (28th May 2015) - Chen, Peng-Cheng; Huang, Xiao-Jun; Xu, Zhi-Kang
<x xml:space="preserve">Abstract</x> The relationships between the activity of immobilized lipase and its adsorption behavior, distribution, and structure were revealed for the first time.